Study of incidence and cause of delay for treatment of long bone fractures of the lower limb in tertiary care hospital - Sada, Elizabeth C.; Bhot, Firdaus; Kanishetty, Rohit (International Surgery Journal, 2019)
Background: Musculoskeletal trauma represents a considerable global health burden. Lower limb long bone fractures are seen as a serious concern at the individual and population level. So the purpose of the study was to find incidence and cause of delay for treatment of long bone fractures of the lower limb in tertiary care hospital. Methods: All adult patients (more than 18 years) reporting to Emergency Medicine Department of a tertiary care hospital with long bone fractures of lower limb were included in the study. Effects on the final outcome on the lifestyle of the patients were evaluated against the interventions and management at all stages of the course of the illness. Delay of surgery: in our study delay of surgery means if surgery occurs after one day (24 hours) of admission. The entire data is statistically analysed using SPSS software. P values less than 0.05 are considered to be statistically significant. Results: 74 operated cases. 60 cases (81.10%) had delayed surgery, 14 cases (18.9.0%) did not have delayed surgery. 33 cases (55%) had medical reason for delay, 19 cases (31.7%) had financial reason for delay, 5 cases (14.3%) had infrastructure issues (unit system/non availability of implant), 3 cases (5.0%) had plan of surgery as causes of delay. Conclusions: These factors have an effect in the final outcome of the cases. The final outcome is dependent on multiple factors. Adequate attention to each and every one of them was long way to get the patient to the pre-incident stage.